Trends in MBA research topics - Thomas, Shibi Mary (My University, 2011)
There is a growing demand for Masters in Business Administration (MBA) postgraduates generally. This need for business leadership is greater in South Africa and throughout the continent of Africa. MBA in South Africa is completed typically with a research report in the final year. This research identifies trends in MBA research topics and research methodologies applied while doing a research. The research methodology used for this study was quantitative analysis, in order to identify any potential trends. Research records done by MBA students were analysed to identify the topics chosen for their research. Further study was conducted to identify the research methodology used within each research record in order to study trends in this area. One of the key findings from the research was that research topics selected by MBA students are based on the topical issues highlighted in the business world. Of the topics selected, there is a shift in topic choice towards softer skills of business. The other substantial finding is the area of management research and research techniques. The finding indicates that researchers are moving from quantitative research techniques to other types of research methodologies. A variety of recommendations are made, based on the findings in this research, to management education institutions, MBA curriculum setters and MBA researchers. A key point is that trends from this research can be used to influence and address skills taught in MBA programmes
MBA - WBS
Keywords: MBA research; Research methodologies